In Vitro Evaluation of Phosphate Adaptability and Solubilization Capacity of Trichoderma Sp Strains at Various Temperatures - Cordero, Alexander Perez; Vergara, Donicer E. Montes; Mendoza, Yelitza Aguas (Journal of Posthumanism, 2024)
The aim of this study was to evaluate in vitro the ability of the isolate Trichoderma viride to grow and solubilize phosphate. Sampling was carried out in avocado soil in the municipality of Chalán in the Mountain of María. Twelve strains of Trichoderma spp. were isolated, which by morphological and structural characteristics identified Trichoderma viride as the predominant strain. The results show that T. viride grew at temperatures of 30, 35 and 40 °C. The spore concentration found at 30°C was 4.5 x 106 spores/mL and at 40°C showed a spore concentration of 1.5 x 106 spores/mL. The phosphate solubilisation capacity of T. viride at 40°C was also demonstrated. The capacity of Trichoderma is variable and depends directly on the strain and its capacity for action. The study predicts the ability of T. viride to adapt to 40°C and retain the ability to solubilize phosphate, which may be an alternative to climate change with increasing temperatures in agricultural systems.